2016
DOI: 10.1186/s12891-016-1356-5
|View full text |Cite
|
Sign up to set email alerts
|

Genes associated with persistent lumbar radicular pain; a systematic review

Abstract: BackgroundThe aim of the present study was to provide an overview of the literature addressing the role of genetic factors and biomarkers predicting pain recovery in newly diagnosed lumbar radicular pain (LRP) patients.MethodsThe search was performed in Medline OVID, Embase, PsycInfo and Web of Science (2004 to 2015). Only prospective studies of patients with LRP addressing the role of genetic factors (genetic susceptibility) and pain biomarkers (proteins in serum) were included. Two independent reviewers extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
(100 reference statements)
0
14
0
Order By: Relevance
“…Earlier data suggest that the heritability of back pain range from 30 to 45% [16]. Genetic variability, which is important for degenerative changes, inflammation or pain perception may play a role in both LBP and LRP conditions [1721]. Genetic variants in genes encoding proteins such as vitamin D receptor (VDR), collagens (COL) and matrix metalloproteinases (MMPs) may affect degeneration of the intervertebral discs [18, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier data suggest that the heritability of back pain range from 30 to 45% [16]. Genetic variability, which is important for degenerative changes, inflammation or pain perception may play a role in both LBP and LRP conditions [1721]. Genetic variants in genes encoding proteins such as vitamin D receptor (VDR), collagens (COL) and matrix metalloproteinases (MMPs) may affect degeneration of the intervertebral discs [18, 22].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we wanted to explore whether or not the genetic polymorphisms of cytokines affect the dosage of PCIA sufentanil after radical lung cancer surgery. After reviewing the available studies, we found that IL-1A, 24,[29][30][31] IL-1β, 24,29,31,32 IL-1RN, 24,29,33 IL-6, 24,29,34,35 CXCL8, 24,29,35,36 IL-10, 24,29 TNF, 20,24,28 NFκB1, 24,29,37 REL 37 and NFκBIA 24,37 are closely related to pain. After searching the NCBI SNP database (http://www.…”
Section: Discussionmentioning
confidence: 99%
“…Other anti-inflammatory cytokines such as IL-1, IL-6, and COX 2 are associated with DDD and pain related to DDD [85]. Systematic Review on genes and biomarkers for pain in DDD shows that five genetic variants; i.e., OPRM1 rs1799971 G allele, COMT rs4680 G allele, MMP1 rs1799750 2G allele, IL1α rs1800587 T allele, IL1RN rs2234677 A allele, were associated with reduced recovery of lower back pain and three biomarkers; i.e., TNFα, IL6 and IFNα, were associated with persistent back pain [86]. In our endoscopic videos analysis, we found the presence of grade 2 and 3 neovascularization associated with all cases which required sinuvertebral and basivertebral nerves ablation.…”
Section: Inflammatory Processesmentioning
confidence: 99%